2020
DOI: 10.21608/ejbo.2020.26785.1478
|View full text |Cite
|
Sign up to set email alerts
|

Investigations on the Prevalence of Two Sweet Potato Viruses and their Potential Weed Reservoirs in Egypt

Abstract: G LOBALLY, sweet potato (Ipomoea batatas (L.) Lam., family Convolvulaceae), is an important vegetable crop, unluckily, the viral infection induces a significant yield loss. The current study aims to identify the viruses infecting sweet potato in Egypt and highlights the role of the interfacing weeds as viruses reservoir. The study covered both of transmission, host range, inclusion bodies, virus morphology, histopathology, serological diagnosis, genome identification using RT-PCR and multiplex RT-PCR. The resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 33 publications
1
2
0
Order By: Relevance
“…The data of bioactive constituents in the current study revealed that SMYEV infection showed a remarkable increase in phenols, indoles, total flavonoids and percentage of acidity in the fruit juice as citric acid. These results were in agreement with those obtained by Mazyad et al (2014) on strawberry plants infected with Strawberry latent ringspot virus (SLRSV). Also, El-Shazly et al (2016) found that Tomato spotted wilt virus infection increased total titratable acidity in infected tomato fruit compared to healthy plants.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The data of bioactive constituents in the current study revealed that SMYEV infection showed a remarkable increase in phenols, indoles, total flavonoids and percentage of acidity in the fruit juice as citric acid. These results were in agreement with those obtained by Mazyad et al (2014) on strawberry plants infected with Strawberry latent ringspot virus (SLRSV). Also, El-Shazly et al (2016) found that Tomato spotted wilt virus infection increased total titratable acidity in infected tomato fruit compared to healthy plants.…”
Section: Discussionsupporting
confidence: 91%
“…This indicates that infection with the virus affects postharvest quality preservation, based on the observation of Rekika et al (2005). Mazyad et al (2014) recorded a noticeable decrease in total anthocyanin and vitamin C contents by SLRSV infection on strawberry fruits. Moreover, Shafie (2019) reported that Hibiscus chlorotic ringspot virus infection significantly decreased the entire anthocyanin content in the sepals of infected roselle plants.…”
Section: Discussionmentioning
confidence: 86%
“…Additionally, there has been very little research on the medicinal value of Egyptian SP cultivars. Thus, our aim was to explore the biological activity and medicinal value of SP, hoping to highlight the promising potential of SP as a cheap, available functional food in the Egyptian market [8]. The importance of SP in the human diet has traditionally been a supply of carbohydrates.…”
Section: Introductionmentioning
confidence: 99%